Penguatan Ketahanan Pangan dan Ekonomi Perempuan Melalui Budidaya Sayuran dan Ikan Dengan Sistem Akuaponik: Integrasi Pengembangan Agrowisata di Desa Bahu Palawa - Atem Atem; Muhammad Zusanri Batubara; Mahmuddin Sirait; Aris Winatama; Doni Dores (Journal of Community Development, 2025)
This community service program aims to provide knowledge, improve skills, and strengthen food security and alternative income for the Bahu Palawa village community, especially the women's group TP PKK Bahu Palawa village. The aquaponic system was chosen because it combines agriculture and fisheries in one sustainable ecosystem, utilizing fish waste as plant fertilizer. The implementation method was carried out through four stages: socialization and counseling, training, technology application, mentoring and evaluation, and program sustainability. The results of this activity for Tim Penggerak  Pemberdayaan Kesejahteraan Keluarga Bahu Balawa Village are increased knowledge and understanding of aquaponic system food cultivation, increased knowledge and skills in designing, building, assembling, and managing aquaponic systems both with a simple model of bucket media (budikdamber) and with the Deep Flow Technique system, increased experience and knowledge of how to cultivate vegetables and fish with new technology that is effectively applied to small land or gardens, increased cooperation, participation and collaboration between members in carrying out work programs, and introduced and provided knowledge to the broader community about food cultivation technology that can be adopted or implemented independently by each household or other groups. This activity is able to become an alternative model of food crop cultivation that encourages household food self- sufficiency, this potential can be seen from the increased knowledge and skills of members group before and after the implementation of education and training from an average score of 48.4% (low) to 83.7% (high), as measured by pre-test and post-test scores, also active participation of 38 members group in the management of aquaponic cultivation.